SCREENING OF SAFFLOWER GERMPLASM ACCESSIONS FOR RESISTANCE SOURCE AGAINST MACROPHOMINA ROOT ROT - SALUNKHE, VANITA NAVNATH (The Bioscan, 2014)
Fifty germplasm accessions of safflower procured from AICRP on safflower, Marathwada Krishi Vidyapeeth, Parbhani, Maharashtra were screened for resistance source against Macrophomina root rot under glasshouse condition. The screening revealed that 4 genotypes viz., GMU-3259, GMU-3262, GMU-3306, GMU-3316 were highly resistant (no seedling infection) whereas 3 genotypes GMU-3265, GMU-3285, GMU-3297 were resistant and recorded upto 1-10% seedling mortality whereas 5 moderately resistant genotypes recorded 11- 30% seedling mortality. Fourteen genotypes were found moderately susceptible and indicated 31-50% seedling mortality whereas rests of the accessions were found susceptible or highly susceptible.